2009
DOI: 10.1021/la902979m
|View full text |Cite
|
Sign up to set email alerts
|

Role of an Amide Bond for Self-Assembly of Surfactants

Abstract: Self-assembly in solution and adsorption at the air-water interface and at solid surfaces were investigated for two amino-acid-based surfactants with conductimetry, NMR, tensiometry, quartz crystal microbalance with monitoring of the dissipation (QCM-D), and surface plasmon resonance (SPR). The surfactants studied were sodium N-lauroylglycinate and sodium N-lauroylsarcosinate, differing only in a methyl group on the amide nitrogen for the sarcosinate. Thus, the glycinate but not the sarcosinate surfactant is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
61
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 33 publications
3
61
1
2
Order By: Relevance
“…Interactions with the Cu surface are apparently due not only to the hydrophobic properties of a molecule but also to the presence of heteroatoms (particularly nitrogen) in its composition or multiple bonds that can form both additional intermolecular bonds between particles of an adsorbate such as SOS and other bonds with the metal surface being protected. Results obtained by other investigators [40,41] are in favor of this version. These investigations demonstrated the impact of the tail groups of SOS molecules on interactions with metal surfaces.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…Interactions with the Cu surface are apparently due not only to the hydrophobic properties of a molecule but also to the presence of heteroatoms (particularly nitrogen) in its composition or multiple bonds that can form both additional intermolecular bonds between particles of an adsorbate such as SOS and other bonds with the metal surface being protected. Results obtained by other investigators [40,41] are in favor of this version. These investigations demonstrated the impact of the tail groups of SOS molecules on interactions with metal surfaces.…”
mentioning
confidence: 70%
“…These investigations demonstrated the impact of the tail groups of SOS molecules on interactions with metal surfaces. For example, the role of amide bonds in the selforganization of surfactants on a gold surface was revealed in [40]. It was shown that sarcosine derivatives form chelate compounds with a metal surface that can induce the polymolecular adsorption of SOS molecules.…”
mentioning
confidence: 99%
“…The micellar association of amphiphilic molecules in water is the result of a delicate balance between hydrophobic and hydrophilic forces. In micelles, the polar head groups align at the micelle-water interface, while the non-polar hydrocarbon chains interact with one another in the micelle core [11][12][13]. This micelle structure is dynamic, with surfactant molecules free to & Kevin F. Morris kmorris@carthage.edu exchange between the micelle and free solution.…”
Section: Introductionmentioning
confidence: 99%
“…Above the CMC, van der Waals interactions between the surfactants' hydrocarbon tails favor micellization, while the repulsion of the polar head groups opposes self-assembly [11,12]. In addition, the atoms in functional groups, like the amide bond found in amino acid-based surfactants, often form intermolecular hydrogen bonds that in turn play an important role in determining the size and shape of surfactant micelles [11][12][13]. Amino acid-based surfactants have become increasingly popular in recent years because they are environmentally benign, abundant, and quite versatile [11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, aminophosphonates [12], amides [13] and urea [14] on the particle surface are expected to facilitate the assembly, amine groups can also be used to introduce charge on the surface [15]. Our goal is to create materials based on such silica nanoparticles with potential applications in sensing, separations of biologically relevant molecules and drug delivery.…”
Section: Introductionmentioning
confidence: 99%